ERCC8 related Cockayne syndrome type-1: A rare entity diagnosed in a Turkish boy : ERCC8 related Cockayne syndrome type-1 - Kocagil, Sinem; Keklikci, Ali Rıza; Aydemir, Yusuf; Çilingir, Oğuz; Aynacı, Sabri; Erzurumluoğlu Gökalp, Ebru; Durak Aras, Beyhan; Artan, Sevilhan (Journal of Surgery and Medicine, 2023)
Cockayne syndrome (CS, OMIM #216400 and OMIM #133540) is a rare, progressive, multisystemic disorder that results in premature aging and cachectic dwarfism. It is an autosomal recessive disorder with a prevalence of 2-2.5 per million. Pathogenic variants detected in the ERCC excision repair 6 (ERCC6) and ERCC excision repair 8 (ERCC8) genes are responsible for molecular pathogenesis. In this case report, an 11-year-old boy with severe microcephaly, growth retardation, loss of subcutaneous fat tissue, neuromotor developmental delay, bilateral cataracts, and facial dysmorphism but without dermal photosensitivity, who had a novel missense variant in trans configuration with a nonsense variant is presented.